Rethinking misbehavior and resistance in organizations - Barnes, Alison; Taksa, Lucy (Emerald, 2012)
This volume challenges understandings of organizational misbehavior by looking beyond traditional conceptions of the nexus between misbehavior and resistance in the workplace. Reconsidering misbehavior from a range of different perspectives and disciplinary traditions, including history, employment relations, sociology, management, entrepreneurship, marketing, legal studies and film studies, chapters examine behaviors not only of workers but also of managers, entrepreneurs and consumers. The book begins with an overview by one of the leading scholars of misbehavior, Stephen Ackroyd, who reviews the study of the phenomenon, followed by conceptual reconsideration of the relationship between misbehavior and resistance in a changing industrial landscape. The remainder of the book traverses dimensions of misbehavior and resistance across time and geographical space through a number of case studies that examine behaviors in a range of different places, industries and sectors. In this way it extends analysis to actors outside of the workers who have largely been the focus of existing studies. The volume will add to the emerging body of evidence that disturbs assumptions of consensus and conformity in organizations.
Keywords: Personnel management.; Organizational behavior.; elektronické knihy; electronic books